1986
DOI: 10.1366/0003702864507972
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Coated Cylindrical Internal Reflection Elements for Investigating Interfacial Phenomena

Abstract: Techniques for coating thin copper films on the surface of cylindrical germanium internal reflection elements are described. These films were then characterized in an aqueous environment. The expected exponential relationship between the depth of penetration of the evanescent wave into water and the thickness of the copper film was verified experimentally. The stability of vacuum-deposited copper coatings was strong enough that the internal reflection element could be exposed to an aqueous solution of a polysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…Water may be accurately subtracted from a spectrum by virtue of the high signal-to-noise ratio and computer manipulations achieved by these FT-IR instruments (Mattson et al, 1975;Griffiths & de Haseth, 1985). Iwaoka et al (1986) showed that the water from fully-hydrated acidic polysaccharide which had adsorbed to a Ge IRE positioned in a Circle cell could be subtracted with sufficient accuracy to detect contaminating (1 %) levels of protein that were present.…”
Section: Discussionmentioning
confidence: 99%
“…Water may be accurately subtracted from a spectrum by virtue of the high signal-to-noise ratio and computer manipulations achieved by these FT-IR instruments (Mattson et al, 1975;Griffiths & de Haseth, 1985). Iwaoka et al (1986) showed that the water from fully-hydrated acidic polysaccharide which had adsorbed to a Ge IRE positioned in a Circle cell could be subtracted with sufficient accuracy to detect contaminating (1 %) levels of protein that were present.…”
Section: Discussionmentioning
confidence: 99%
“…A modification of this technique involves the deposition of a thin film of metal onto the surface of the internal reflection element (IRE). If the metallic film is thin enough, the energy transmission of the IRE remains sufficiently high to allow the detection of substances at the liquid-metal interface (13,14).…”
mentioning
confidence: 99%
“…The application of attenuated total reflection infrared spectroscopy-Fourier transform infrared spectroscopy (FT-IR) to studies of corrosion became apparent when it was shown that the intensity of the water absorbance band at 1,640 cm-1 was extremely sensitive to changes in the thickness of the Cu film, as differences of as little as 3 to 4 A (0.3 to 0.4 nm), equivalent to two to three atomic layers of copper, produced detectable changes in the absorbance band at 1,640 cm-' (2,13,17). Attenuated total reflection infrared * Corresponding author.…”
mentioning
confidence: 99%
“…Studies using Cu‐coated IREs and ATR/FTIR indicate that bacterially produced acidic EPS could destabilize Cu films (Jolley et al, 1989; Geesey et al, 1987). Different bacterial EPSs appeared to have different abilities to bind Cu ions (Bremer & Geesey, 1993; Geesey, 1991; Geesey et al, 1986) and induce different Cu oxidation states (Jolley et al, 1988; Iwaoka et al, 1986). A Cu concentration cell was proposed to form as a result of different bacterial species within a biofilm excreting EPS with different binding affinities for Cu ions.…”
Section: Laboratory and Field Simulations Of Micr0bially Influenced Pmentioning
confidence: 99%